PENGARUH KINERJA KEUANGAN DAN VARIABEL MAKRO EKONOMI TERHADAP HARGA SAHAM PERUSAHAAN PERTAMBANGAN - Purnama, Ida Bagus Adytiem; Purbawangsa, Ida Bagus Anom (E-Jurnal Manajemen, 2017)
This study aims to determine the effect of the financial performance and macroeconomic variables on stock prices. Financial performance in this study is proxied by the current ratio, debt to equity ratio, net profit margin, and earnings per share. Macroeconomic variables is proxied by interest rates and GDP growth. The sampling method in this study using census method with non-probability sampling techniques. Mining companies as the study population and obtain a sample of 28 samples. The study period is 2013 - 2015. Multiple linear regression analysis used in this study as data analysis techniques. The results of the data analysis found that the current ratio, debt to equity ratio, earnings per share, and GDP growth has a positive and significant impact on prices stock. Net profit margin and interest rates has no significant impact on the company's stock price.
Keywords: financial performance; macro-economic; financial ratios; fundamental analysis; stock prices